2007
DOI: 10.1073/pnas.0700154104
|View full text |Cite
|
Sign up to set email alerts
|

EDEM1 reveals a quality control vesicular transport pathway out of the endoplasmic reticulum not involving the COPII exit sites

Abstract: Immature and nonnative proteins are retained in the endoplasmic reticulum (ER) by the quality control machinery. Folding-incompetent glycoproteins are eventually targeted for ER-associated protein degradation (ERAD). EDEM1 (ER degradation-enhancing ␣-mannosidaselike protein 1), a putative mannose-binding protein, targets misfolded glycoproteins for ERAD. We report that endogenous EDEM1 exists mainly as a soluble glycoprotein. By high-resolution immunolabeling and serial section analysis, we find that endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(115 citation statements)
references
References 47 publications
11
104
0
Order By: Relevance
“…In support of this, electron microscopy showed that EDEM1 is primarily localized in double-membrane buds that form outside canonical ER exit sites, known as EDEMosomes (Zuber et al 2007;Le Fourn et al 2009;Reggiori et al 2010). At steady state, short-living ERAD components like EDEM1 and OS-9 appeared to be engulfed in these buds in a COPII-independent manner and degraded without the attachment of nonlipidated LC3.…”
Section: Other Degradation Pathwaysmentioning
confidence: 79%
“…In support of this, electron microscopy showed that EDEM1 is primarily localized in double-membrane buds that form outside canonical ER exit sites, known as EDEMosomes (Zuber et al 2007;Le Fourn et al 2009;Reggiori et al 2010). At steady state, short-living ERAD components like EDEM1 and OS-9 appeared to be engulfed in these buds in a COPII-independent manner and degraded without the attachment of nonlipidated LC3.…”
Section: Other Degradation Pathwaysmentioning
confidence: 79%
“…1B, lane 1). As previously demonstrated (30), this heterogeneity was due to the inefficient recognition of its five glycosylation sites, as the protein doublet coalesced as a single band upon Endo H treatment (Fig. 1B, lane 2).…”
Section: Post-translational N-linked Glycosylation Of the C-terminal mentioning
confidence: 62%
“…When the glucosidase inhibitor DNJ was added to remove any heterogeneity created by glucose trimming, EDEM1-S626A migrated with the same mobility as the lower band observed with the WT doublet that corresponded to EDEM1 containing four glycans (Fig. 1B, lanes 7 and 8) (30).…”
Section: Post-translational N-linked Glycosylation Of the C-terminal mentioning
confidence: 97%
See 2 more Smart Citations